Sociocultural variables have a major impact on participation in patients treated for paediatric posterior fossa tumours. (22nd June 2022) - Hoffmann‐Lamplmair, Doris; Gram, Alexandra; Krottendorfer, Kerstin; Peyrl, Andreas; Leiss, Ulrike; Czech, Thomas; Slavc, Irene; Pletschko, Thomas
Abstract: Background: This study investigates the severeness of participation barriers in patients surviving paediatric posterior fossa tumours (PFT) many years after treatment. In the past, aetiological studies on adverse outcome have primarily focused on pathobiological risk factors. The current analysis aims to investigate the importance of environmental variables. Methods: On average, 10 years after diagnosis, educational and social difficulties of 42 patients surviving paediatric PFT (mean age 17 years) were inquired using a self‐constructed questionnaire following the Psychosocial Resource‐Orientated Assessment (PREDI). Educational or social participation barriers were defined by self‐ and/or proxy‐reported difficulties in school or in peer relationships. Accordingly, the children and adolescents were categorized into groups of adequate and limited participation. Subsequently, the study identified potential pathobiological (treatment type, hydrocephalus, tumour relapse, gender, age at diagnosis, seizures and cerebellar mutism) and environmental (parental and maternal education, siblings, main language, discrepancies between personal and environmental values, regular physical activity and private living space) risk factors and investigated whether patients with adequate and limited participation differed in the number of risk factors. Results: Almost one decade after treatment, two thirds of patients experienced educational and/or social difficulties. Patients with limited participation were more frequently associated with environmental factors such as low maternal education degree, siblings, main language other than German, discrepancies between societal and personal values and irregular physical activity, as well as the pathobiological risk factors treatment type, hydrocephalus, tumour relapse, cerebellar mutism and seizures. These variables significantly discriminated between patients with and without limited participation. Conclusions: Limited participation in patients treated for paediatric PFT is common. Next to pathobiological, also environmental risk factors play a major role in educational and social participation barriers. This highlights the fact that solely considering pathobiology is not sufficient when investigating risk factors for the emergence of late sequelae. Future aetiological studies must adopt a biopsychosocial perspective.